Negotiations Between the Center and the Margin: Hanif’s Red Birds as a Transcultural Contact Zone - Muddassar Ali; Dr. Ali Usman Saleem (Journal of Management Practices, Humanities and Social Sciences, 2024)
Transculturation utilizes the contact zone as a productive literary and analytical space in which a third-world writer negotiates between Western and non-Western sensibilities, appropriates Western materials for self-representations, and problematizes Euro-American hegemonic discourses. This paper employs Pratt’s ideas of contact zone and transculturation as its theoretical framework to examine how Hanif adopts transculturation as the medium for negotiation, appropriation, and transformation in Red Birds to challenge Eurocentrism and to question the binary of western self and Muslim other in backdrops of 9/11 and War on Terror. This qualitative research primarily analyzes Red Birds as a transcultural negotiation between American and Muslim subjects. It is found that Hanif, as a transcultural fiction writer, appropriates postmodern rejection of hegemonic metanarratives for constructing self-representations to speak back to the west from the position of marginality. By employing Belsey’s proposed research method of textual analysis, we read Red Birds as a contact zone and establish that Hanif inverts the conflict of War on Terror between the Americans and the Muslims into a contact zone to imagine the possibilities of their coexistence. The paper foregrounds the disruption of Eurocentric discourses of global security and Western/Muslim binary to suggest that Pakistani Anglophone fiction has moved beyond the constraints of 9/11 discourses.